Students as victims of bullying by teachers : Longitudinal antecedents and consequences - Strohmeier, Dagmar; Trach, Jessica; Chavez, Daniela; Urso, Giulio (Springer Nature, 2025)
The longitudinal associations of bullying by teachers with (a) social and academic student characteristics, (b) supportive relationships with peers and adults, and (c) the school context were investigated. Three waves of data were collected over two years among 630 adolescents in Austria (50% girls; 78.8% non-immigrants; mean age = 12.52 years, SD = 0.67). Controlling for the nested data structure at class level, a series of cross lagged panel models controlling for gender, immigrant status, and age were conducted. Social student characteristics (e.g., high levels of peer victimization and high levels of peer bullying) were concurrent, but not longitudinal risk factors for being bullied by teachers. Academic student characteristics (e.g., low levels of school motivation and low levels of learning interest) were longitudinal risk factors for being bullied by teachers, but high levels of supportive peer relationships and high levels of school bonding were longitudinal protective factors. Low levels of perceived support from adults were both an antecedent and a consequence of teacher bullying. Bullying by teachers should be integrated into bullying prevention programs.